2016
DOI: 10.1007/s11064-016-2134-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nerve Growth Factor and Basic Fibroblast Growth Factor Promote Human Dental Pulp Stem Cells to Neural Differentiation

Abstract: Dental pulp stem cells (DPSCs) were the most widely used seed cells in the field of neural regeneration and bone tissue engineering, due to their easily isolation, lack of ethical controversy, low immunogenicity and low rates of transplantation rejection. The purpose of this study was to investigate the role of basic fibroblast growth factor (bFGF) and nerve growth factor (NGF) on neural differentiation of DPSCs in vitro. DPSCs were cultured in neural differentiation medium containing NGF and bFGF alone or com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 47 publications
0
38
0
1
Order By: Relevance
“…The individual effect of bFGF and NGF has been validated in our prior studies [33,84]. Studies have indicated that co-administration of NGF and bFGF together could synergistically promote tissue reinnervation and neural differentiation, compared with bFGF and NGF alone [85,86]. In this study, we evaluated the effectiveness of dual GF administration for the first time in peripheral nerve injuries, and focused on showing how HP hydrogel can augment this therapy strategy.…”
Section: Discussionmentioning
confidence: 91%
“…The individual effect of bFGF and NGF has been validated in our prior studies [33,84]. Studies have indicated that co-administration of NGF and bFGF together could synergistically promote tissue reinnervation and neural differentiation, compared with bFGF and NGF alone [85,86]. In this study, we evaluated the effectiveness of dual GF administration for the first time in peripheral nerve injuries, and focused on showing how HP hydrogel can augment this therapy strategy.…”
Section: Discussionmentioning
confidence: 91%
“…Dental pulp MSCs demonstrate immunomodulatory properties partly attributable to their expression of IL-8, IL-6, and TGF-β, which could inhibit T cell function [139,140]. Moreover, dental pulp MSCs secrete many neurotrophic factors like BDNF [141], glial cell linederived neurotrophic factor [142], and NGF [143]. Although dental pulp MSCs and SHED originate from dental pulpal tissues and share many common properties, SHED demonstrated a higher proliferation rate but lower osteogenic potential as compared to dental pulp MSCs [144].…”
Section: Dental Pulp Mesenchymal Stem/progenitormentioning
confidence: 99%
“…Studies have confirmed that VEGF and BFGF can promote the proliferation, differentiation, and migration of embryonic neural stem cells by activating transcription factors, and have direct neuroprotective and neurotrophic effects on neurons and glial cells . In addition, Hawkins et al found that vascular endothelial cells also form a natural barrier that selectively blocks the invasion of exogenous substances while delivers nutrients to neural stem cells .…”
Section: Discussionmentioning
confidence: 97%